Prothrombin Activation Is Increased among Asymptomatic Carriers of the Prothrombin G20210A and Factor V Arg506Gln Mutations - Bauer, Kenneth A.; Humphries, Steve; Smillie, Belinda; Li, Lily; Cooper, Jacqueline A.; Barzegar, Samad; Rosenberg, Robert D.; Miller, George J. (Thrombosis and Haemostasis, 2000)
The risk of venous thrombosis is increased in individuals who carry specific genetic abnormalities in blood coagulation proteins. Among Caucasians, the prothrombin G20210A and factor V Arg506Gln (FV R506Q) mutations are the most prevalent defects identified to date. We evaluated their influence on markers of coagulation activation among participants in the Second Northwick Park Heart Study, which recruited healthy men (aged 50–61 years) from nine general medical practices in England and Wales. They were free of clinical vascular disease and malignancy at the time of recruitment. Genotypes for the two mutations were analyzed using microplate array diagonal gel electrophoresis, and coagulation markers (factor XIIa; activation peptides of factor IX, factor X, and prothrombin; fibrinopeptide A) were measured by immunoassay. Factor VII coagulant activity and factor VIIa levels were determined by a functional clotting assay. Among 1548 men genotyped for both mutations, 28 (1.8%) and 52 (3.4%) were heterozygous for prothrombin G20210A and FV R506Q, respectively. The only coagulation marker that was significantly associated with the two mutations was prothrombin activation fragment F1+2 [mean ± SD, 0.88 ± 0.32 nmol/L in men with prothrombin G20210A (p = 0.002) and 0.89 ± 0.30 in men with FV R506Q (p = 0.0001) versus 0.72 ± 0.24 among non-carriers for either mutation]. This data provides conclusive evidence that heterozygosity for the prothrombin G20210A as well as the FV R506Q mutations in the general population leads to an increased rate of prothrombin activation in vivo.
Keywords: Prothrombin G20210A; factor V-Arg506Gln; coagulation activation markers; prothrombin activation fragment F1+2